Moisture damage analysis for an asphalt mixture through the MIST test and the iPAS 2D® software - Figueroa Infante, Ana Sofía (2025)
Moisture Damage is one of the most common problems in asphalt pavements roads in tropical countries and in areas exposed to prolonged periods of rain. This research presents the results of moisture damage in a dense asphaltic mixture, which was designed by the Superpave® methodology and manufactured with eight types of asphalt, subjected to a controlled process of oxidation. In addition, the results of the performance of the asphalt mixture and their relation with moisture damage in Moisture Induced Sensitivity Test-MIST and its analysis using the iPAS 2D® software, which was developed by the MARC Group from the University of Wisconsin-Madison and led by the Professor Hussain Bahia.  The results indicate a higher loss of tensile strength when the mixtures are tested with the MIST test compared with the Tensile Strength Ratio-TSR test.  Similarly, the images analysis shows the evolution of loss of contact of the aggregates according to the different periods of oxidation of the asphalts and its relation with the MIST analysis.